Determination of Tutor Rewards Using the Profile Matching Method - Anton Setiawan Honggowibowo; Astika Ayuningtyas (PT FORMOSA CENDEKIA GLOBAL, 2022)
Teachers are the spearhead to improve the quality of education because whether or not the quality of education is good or not, one of which will be determined by the teacher himself. Therefore, teachers need to be motivated and enthusiastic to teach more actively and diligently to share their knowledge with their students. In the learning process, teachers are required to be able to make innovations because students have their own uniqueness, so teachers are expected to be able to meet the needs of students in obtaining learning. The activities and workload of teachers in the world of education are currently increasing. The existence of awards in the form of rewards can increase the motivation of teachers in carrying out their duties and obligations. The criteria for a good teacher are not only seen from the criteria for education and experience, but other criteria are needed such as personality competence, pedagogical competence and social competence. These criteria will be the benchmark in selecting teachers who will receive rewards. The existence of an effective decision-making system to facilitate the determination of tutor rewards. The profile matching method is applied to obtain ranking search results that show the highest to the lowest scores for each teacher, from the ranking results, teachers are selected who will get rewards. The implementation of a website-based tutoring teacher reward application using the profile matching method can run well.